REAL WORLD IMPLEMENTATION OF TREAT-TO-TARGET IN PATIENTS WITH IBD IN A LEARNING HEALTH SYSTEM: AN IBD QORUS COLLABORATIVE STUDY. (26th January 2023) - Singh, Siddharth; Oliver, Brant; Hou, Jason; Lum, Donald; van Deen, Welmoed; Weaver, Alandra; Siegel, Corey; Melmed, Gil
Abstract: BACKGROUND AND AIMS: A treat-to-target (TTT) strategy of aiming for symptomatic and endoscopic remission is recommended for the management of inflammatory bowel diseases (IBD). Yet, real-world uptake of TTT strategies has been modest. We sought to assess the feasibility of implementing TTT and improve its uptake in the Crohn's and Colitis Foundation's IBD Qorus learning health system (LHS). METHODS: We examined an 'intention to TTT' for each eligible clinic visit (patients not in endoscopic remission on most recent evaluation) across a multi-center LHS over a 12-month period (November 2020-November 2021). 'Intention to TTT' (or TTT score) was defined as an affirmative response to all three of the following: (1) Was treat-to target discussed with patient?, (2) Was objective assessment for inflammation (endoscopy, radiology and/or fecal calprotectin) performed within the preceding 12m?, (3) Is there an intention to change treatment since target has not been reached? Over a 12-month breakthrough series (BTS) collaborative, we sought to improve implementation of TTT with monthly report cards, webinars, an active listserv and two all-Qorus learning sessions. Changes in rates of 'intention to TTT' were examined over 12 months, overall and at each site, with an earliest clinically meaningful signal of improvement defined a priori as 2% increase per month. In secondary analyses, we compared overall rates of achieving endoscopic remission and corticosteroid-free clinical remission in sites with improvement in rates of 'intention to TTT' relative to sites without improvement (only sites with valid data for 8/12 months). RESULTS: Over 12 months, there were 7934 patient visits across 38 sites in the collaborative; patients in 37% visits (n=2913) were not in endoscopic remission at time of visit. Overall, rates of 'intention to TTT' increased from 23% at the beginning of the BTS, to 49% at the end of the BTS, corresponding to a clinically significant 2.4% per month increase in rates of implementing TTT (Figure 1). While rates of discussion of TTT (88% of eligible visits) and intending to adjust therapy (70% of eligible visits) were consistently high, there was a significant increase in objective evaluation for inflammation during the course of the BTS. There was considerable variability across sites in rates of 'intention to TTT'. Comparing 9/14 sites with improvement in rates of implementing TTT vs. 5/14 sites without improvement, there were trends towards increasing rates of site-level endoscopic remission and steroid-free clinical remission (Figure 2). CONCLUSIONS: Through a quality improvement initiative in a LHS, rates of 'intention to TTT' increased significantly over 12-months. This improvement in implementation of TTT was accompanied by increase in rates of achieving endoscopic remission and steroid-free clinical remission.